Investigating Suspected Professional Lenders Features Based on Large Scale Judgment Texts of China - Gu, Songyuan; Huang, Ting; Huang, Xiaohan; Wang, Ruikun; Li, Xin (International Conference on Computer Science & Education, 2021)
In recent years, there have been frequent chaos in professional lending, and professional lenders are in a stage of strict regulation. At present, most provinces lack specific determination standards for the professional lenders in judicial practice, and the data research on the phenomenon of professional lenders lacks global and diachronic analysis. Based on more than 5 million judgment texts, the number of litigation involved by the same party is used as the identification standard, and the number of litigation involved 5 or more is included as the index to establish a case database of suspected professional lenders. Based on the case database of suspected professional lenders, we conduct an exploratory analysis of the dimensions of region, gender, age and the number of litigation involved. The results show that the regional distribution of suspected professional lenders is mainly concentrated in the eastern region, and the proportion of males is higher than that of females, and the majority are the middle-aged and middle-aged elderly. However, the number of litigation involved does not subject to power-law distribution.